PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS MODEL CORE (CONNECTING, ORGANIZING, REFLECTING AND EXTENDING) PADA POKOK BAHASAN IKATAN KIMIA SMA/MA KD 3.5 DAN 4.5 - Cahyani, Widya; Susilawati, Susilawati; Noer, Asmadi M (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The objective of this research was to develop the student worksheet on the subject of chemical bonds. The type of this research was reserach and development (R & D) with the ADDIE development models which include analysis, design, development, implementation and evaluation. This research was carried out to the implementation stage, namely one-on-one trials and limited trials. The study was conducted at the University of Riau FKIP. The object of research is (Connecting, Organizing, Reflecting dan Extending) CORE-based student worksheet. The data analysis technique used in the study is descriptive statistical analysis, which is by calculating the percentage of validation values. The average score of the assessment of the five aspects of student worksheet eligibility by the validator team, namely the feasibility of the content, characteristics of the CORE model, linguistic, presentation, and graphic values were 91.67%, 93.75%, 90.00%, 91.67% and 85.41%, respectively. so, the overall average score of the chemical bond student worksheet validation based on the CORE model is in the valid eligibility category, meaning that the developed student worksheet is feasible to use. While the percentage of teacher and student responses to student worksheet was 92.85% and 91.90% which were on positive criteria. Â Â Key Words: Student Worksheet (SWs), CORE models, and Chemical Bonds.